Estimating an Auction Platform Game with Two-Sided Entry - Marra, Marleen (Journal of Political Economy, 2025)
This paper develops and estimates a structural auction platform model with endogenous entry of buyers and sellers to study the welfare impacts of fee changes. Estimates from a new wine auction dataset illustrate the striking feature of two-sided markets that some users can be made better off despite paying higher fees. The results also underscore the importance of addressing seller selection when endogenizing (buyer) entry onto auction platforms. Quantifying the welfare effects from (anticompetitive) fee changes through a model that accounts for important user interactions enables antitrust policy to be applied to such markets.